السیاسة الجنائیة للمشرع الجزائري في مكافحة - رندة سوقال; إيناس علي بوعشة (My University, 2020)
Summary: The crime of bribery is one of the oldest and most serious corruption crimes in international societies, and it has become a serious topic of concern. This is why the Algerian legislature has initiated the drafting of legal texts to inform it. It had been incorporated into the Penal Code previously but had not succeeded in reducing it. rather, it is becoming increasingly increasing, prompting the legislator to change his criminal policy, but it has become a global subject that has received the attention of international and regional agreements. As Algeria has become an active and active member of the international community, In keeping with all its development, it has endeavoured to develop a comprehensive strategy through the development of new laws derived from its integration and involvement in international relations. It issued a 06-01 dated 2006/2/20 after it ratified the United Nations Agreement. strategy ", which is the first international mechanism to develop a comprehensive anti-corruption strategy, in particular bribery through the enactment of a series of effective measures to eliminate and reduce it The Algerian legislature has enshrined its provisions in this Act and has become the most important national instrument for countering corruption crimes and establishing them as a crime of bribery. Act No. 06-01 defines a public official more accurately as well as the definition of foreign and private employees, and all that would make the crime of bribery and adopted a bribery binary doctrine because of its advantages. to ensure that the perpetrator is not impunity, whether Rachid or Marachi, The development of sophisticated follow-up procedures in view of the evolution of the crime and its methods and supported by institutional structures, the most important of which was reflected in the National Body for Preventing and Combating Corruption, mandated to develop a national strategy to prevent corruption civil society should encourage the media to work to combat corruption crimes, Believing in their active role in raising awareness of the dangers of bribery, the legislature has recruited all the oppressive, deterrent and even awareness means necessary to combat the crime of bribery, But we still see it in all our surroundings, and we hope that it will disappear in the near future. ....................... اﻟﻣﻠﺧص : ﺗﻌد ﺟرﯾﻣﺔ اﻟرﺷوة ﻣن أﻗدم وأﺧطر ﺟراﺋم اﻟﻔﺳﺎد اﻟﺗﻲ اﺳﺗﻔﺣﻠت ﻓﻲ اﻟﻣﺟﺗﻣﻌﺎت اﻟدوﻟﯾﺔ، ﻓﺄﺻﺑﺣت ﺑذﻟك ﻣن اﻟﻣواﺿﯾﻊ اﻟﺟدﯾرة ﺑﺎﻻﻫﺗﻣﺎم، ﻫذا ﻣﺎ ﺟﻌل اﻟﻣﺷرع اﻟﺟزاﺋري ﯾﺑﺎدر ﺑوﺿﻊ ﻧﺻوص ﻗﺎﻧوﻧﯾﺔ ﻟﻺﺣﺎطﺔ ﺑﻬﺎ، ﻓﺄدرﺟﻬﺎ ﻓﻲ ﻗﺎﻧون اﻟﻌﻘوﺑﺎت ﺳﺎﺑﻘﺎ ﻟﻛﻧﻪ ﻟم ﯾﻔﻠﺢ ﻓﻲ اﻟﺣد ﻣﻧﻬﺎ، ﺑل أﻧﻬﺎ أﺻﺑﺣت ﺗﺗزاﯾد أﻛﺛر فأكثر ، ﻣﻣﺎ دﻓﻊ اﻟﻣﺷرع اﻟﻰ ﺗﻐﯾﯾر ﺳﯾﺎﺳﺗﻪ اﻟﺟﻧﺎﺋﯾﺔ ﺑل أﺻﺑﺣت ﻣوﺿوع ﻋﺎﻟﻣﯾﺎ ﺣظﻰ ﺑﺎﻫﺗﻣﺎم اﻻﺗﻔﺎﻗﯾﺎت اﻟدوﻟﯾﺔ واﻻﻗﻠﯾﻣﯾﺔ، وﺑﻣﺎ أن اﻟﺟزاﺋر اﺻﺑﺣت ﻋﺿوا ﻓﺎﻋﻼ وﻧﺎﺷطﺎ ﻓﻲ اﻟﻣﺟﺗﻣﻊ اﻟدوﻟﻲ ، تساير وتواﻛب ﻛل ﺗطوارﺗﻪ، ﺳﻌت اﻟﻰ وﺿﻊ اﺳﺗراﺗﯾﺟﯾﺔ ﺷﺎﻣﻠﺔ ﻣن ﺧﻼل اﺳﺗﺣداث ﻗواﻧﯾن ﺟدﯾدة ﻣﺳﺗﻧﺑطﺔ ﻣن اﻧدﻣﺎﺟﻬﺎ واﻧﺧراطﻬﺎ ﻓﻲ اﻟﻌﻼﻗﺎت اﻟدوﻟﯾﺔ، حيث أصدرت ق و ف م 06-01 المؤرخ في 2006/2/20 وذﻟك ﺑﻌد ﻣﺻﺎدﻗﺗﻬﺎ ﻋﻠﻰ اﺗﻔﺎﻗﯾﺔ اﻻﻣم المتحدة ،اﻟﺗﻲ ﺗﻌﺗﺑر أول آﻟﯾﺔ دوﻟﯾﺔ وﺿﻌت اﺳﺗراﺗﯾﺟﯾﺔ ﺷﺎﻣﻠﺔ ﻟﻣﻛﺎﻓﺣﺔ اﻟﻔﺳﺎد ،لا سيما الرشوة من خلال سن مجموعة من التدابير الفعالة للقضاء عليها والحد منها ،ﻓﻛرس اﻟﻣﺷرع اﻟﺟزاﺋري اﺣﻛﺎﻣﻬﺎ ﺿﻣن ﻫذا القانون وأﺻﺑﺢ أﻫم أداة وطﻧﯾﺔ ﻟﻣواﺟﻬﺔ ﺟراﺋم اﻟﻔﺳﺎد وﻋﻠﻰ أرﺳﻬﺎ ﺟرﯾﻣﺔ اﻟرﺷوة. ﻓﺟﺎء ﻓﻲ ﻗﺎﻧون 06-01 تعريف الموظف العمومي بدقة أكثر ، وكذا تعريف الموظف الأجنبي والموظف في القطاع الخاص ، وﻛل ﻣﺎ ﻣن ﺷﺄﻧﻪ ان ﯾﻘوم ﺑﺟرﯾﻣﺔ اﻟرﺷوة، ﻛﻣﺎ ﻣﯾزﻫﺎ ﻋن ﻏﯾرﻫﺎ ﻣن الجرائم ، وﺗﺑﻧﻰ ﻣذﻫب ﺛﻧﺎﺋﯾﺔ ﺟرﯾﻣﺔ اﻟرﺷوة ﻟﻣﺎ ﻟﻪ ﻣن مزاﯾﺎ ﻛﺎن ، ﺗﻛﻔل ﻋدم إﻓﻼت اﻟﺟﺎﻧﻲ ﻣن اﻟﻌﻘﺎب ﺳواء كان راشيا أو مرتشيا ، واﺳﺗﺣداث ﺿﻣن ﻧﺻوﺻﻪ إﺟراءات ﻣﺗﺎﺑﻌﺔ ﻣﺗطورة ﻧظرا ﻟﺗطور اﻟﺟرﯾﻣﺔ وأﺳﺎﻟﯾﺑﻬﺎ، ودﻋم ذﻟك ﺑﻬﯾﺎﻛل ﻣؤﺳﺳﺎﺗﯾﺔ ﺗﺟﺳدت أﻫﻣﻬﺎ ﻓﻲ اﻟﻬﯾﺋﺔ اﻟوطﻧﯾﺔ ﻟﻠوﻗﺎﯾﺔ ﻣن اﻟﻔﺳﺎد وﻣﻛﺎﻓﺣﺗﻪ ، التي أوكلت لها مهمة وﺿﻊ اﺳﺗراﺗﯾﺟﯾﺔ وطﻧﯾﺔ ﻟﻠوﻗﺎﯾﺔ ﻣن اﻟﻔﺳﺎد، وﯾﻌد أﻫم ﻣﺎ ﺗﺿﻣن ق 06-01 هو ضرورة تشجيع المجتمع المدني الإعلام للعمل على محاربة جرائم الفساد، وذلك إﯾﻣﺎﻧﺎ ﻣﻧﻪ ﺑدورﻫﻣﺎ اﻟﻔﻌﺎل ﻓﻲ اﻟﺗوﻋﯾﺔ ﺑﻣﺧﺎطر اﻟرﺷوة، وﺑﻬذا ﯾﻛون اﻟﻣﺷرع ﻗد ﺟﻧد ﻛل اﻟوﺳﺎﺋل اﻟﻘﻣﻌﯾﺔ واﻟردﻋﯾﺔ وﺣﺗﻰ اﻟﺗوﻋوﯾﺔ اﻟﻼزﻣﺔ ﻟﻣﻛﺎﻓﺣﺔ جريمة الرشوة ، إﻻ أﻧﻧﺎ ﻻ ﻧزال ﻧراﻫﺎ ﻓﻲ ﻛل ﻣﺣﯾطﻧﺎ ، ونأمل في أن تختفي منه في المستقبل القريب . ...................... Résumé Le crime de corruption est l'un des crimes les plus anciens et les plus dangereux qui s'est intensifié dans les sociétés internationales, devenant ainsi de plus en plus l'un des sujets dignes d'attention, cela a incité le législateur à modifier sa politique pénale à cet égard, car il ne s'agit plus seulement d'un problème interne, mais plutôt d'un problème mondial qui a attiré l'attention des conventions internationales et régionales, et depuis que l'Algérie est devenue un membre efficace et actif de la communauté internationale qui suit le rythme de tous ses développements, elle a développé une stratégie globale de lutte contre la corruption à travers l’introduction d’une nouvelle loi sur la prévention et la lutte contre la corruption N°06-01, du 20/02/2006. Et ce, après sa ratification de la convention des Nations Unies, qui est le premier mécanisme international à avoir développé une stratégie globale de lutte contre la corruption, en adoptant un ensemble de mesures efficaces pour l’éliminé, le législateur algérien a consacré ses dispositions à cette loi, est devenu l'outil national le plus important pour lutter contre les crimes de corruption.